Hubungan Kecemasan Ibu Bersalin Dengan Pelaksanaan IMD Pada Saat Pandemi Covid-19 Di UPTD Puskesmas Hilisimaetano Tahun 2021 - Tiarnida Nababan; Justri Karniwati Br Surbakti; Rizky Annisa; Noni Hairani; Dorma A Bakara (STIKes Santa Elisabeth Medan, 2021)
fear that is not clear, accompanied by feelings of uncertainty, insecurity, helplessness and isolation. An increased level of anxiety is a mental health problem that often occurs during a pandemic, including the ongoing Covid-19 pandemic. The implementation of IMD during the COVID-19 pandemic is a dilemma, because maternity mothers feel anxious so that IMD actions are difficult to carry out. The aim of the study was to determine the relationship between maternal anxiety and the implementation of IMD during the Covid-19 pandemic. The research method used is descriptive quantitative with a cross sectional design. Research Location At UPTD Puskesmas Hilisimaetano in 2021. The total population in this study amounted to 27 people. Sampling by incidental sampling, the number of samples in the study was 27 people. Collecting data in this study using primary data and secondary data using a questionnaire sheet. The results showed that the majority of respondents had moderate anxiety, which amounted to 13 people (48.1%) of which all 13 respondents were carried out by IMD. In respondents who have a severe level of anxiety, which is 11 people (40.7%), the majority are not implementing IMD, which is 6 respondents and 5 respondents still carry out IMD. And the minority of respondents with mild anxiety amounted to 3 respondents (11.1%) where all of them carried out IMD. The results of the chis-quare test obtained the Asymp value. Sig. (2-sided), with a value of 0.004. The conclusion is there is a relationship between maternal anxiety and the implementation of IMD during the covid-19 pandemic at the uptd health center hilisimaetano in 2021. Suggestions are expected for health workers to provide clear information about IMD and covid-19.